(untitled) (Jurnal Teknologi (Sciences & Engineering), 2025)
Researchers are increasingly exploring sustainable bioresources and eco-friendly energy technologies for wastewater treatment. Microbial fuel cells (MFCs) are a promising green technology that generates energy while treating wastewater. A key component of MFCs is membrane technology, particularly ion exchange membranes (IEMs), which act as separators and facilitate ion transport to improve treatment efficiency and power output. Modifications to IEMs depend on their intended role in MFCs. This bibliometric study aims to quantitatively and qualitatively review research on IEM applications in MFCs from 2014 to 2024 using data from the Scopus database. The Scopus database yielded 501 applicable publications in the last decade, which was the most fruitful timeframe, with research articles accounting for 73.2% of the total. Several categories including total publications and citations history, distribution of subject categories, top journals, countries, and authors were analysed in this analysis. Environmental science leads the subject categories with a majority contribution of 27% for each. However, the energy fuel category has seen the greatest total expansion over the last ten years. Bioresource Technology also published a higher number of papers in MFCs research, with 26.8%. Ion exchange membrane reviews, nanocomposite membranes, developments in electrodes and membranes, ceramics operation, graphene electrodes and power enhancement are the most popular membrane topics discussed in MFCs research. MFC’s separators are often made from perfluorinated ion-exchange membranes like Nafion, a widely used commercial option. However, composite biobased polymer membranes containing organic and inorganic additives are more cost-effective and biocompatible alternatives that can improve ionic conductivity.